Incidental imaging detection of Kartagener syndrome in a female: A case report - Natasha Dhakal, MBBS; Prajwal Dahal, MD (Radiology Case Reports)
Kartagener syndrome is a rare ciliopathic genetic disorder characterized by a triad of chronic sinusitis, situs inversus, and bronchiectasis. The underlying pathophysiology involves reduced ciliary motility due to defects in ciliary structure and function within the respiratory tract and fallopian tubes. Diagnosis is typically confirmed through imaging studies such as X-rays, CT scans, and echocardiograms, which reveal the abnormal orientation of the heart and other organs. Treatment depends on the presence of associated conditions, such as congenital heart defects, respiratory infections and appropriate interventions with regular follow-up can help prevent complications. In this case, we present a 32-year-old female with a history of secondary infertility who presented with recurrent cough and fever. A thorough clinical examination was conducted, followed by radiological investigations that revealed chronic sinusitis, bronchiectasis, dextrocardia, and situs inversus totalis. She was subsequently treated with oral antibiotics, mucolytics, and initiated on chest physiotherapy. This case highlights the importance of considering Kartagener syndrome in patients presenting with recurrent respiratory infections and fertility issues.